The Optimization of Power BI Utilization in JDE’s Financial Reporting and Analysis Practices in Order to Increase Efficiency and Create Higher Quality Reports - Mevina Noviani Rahmatharun (iBuss Management, 2023)
This research examines how Microsoft's Power BI may be used to improve financial reporting and analysis procedures in Jacobs Douwe Egberts (JDE). Each of the seven chapters in the report addresses different topics relating to Power BI's core features, best practices, JDE’s current financial practices, user requirements and problems, integration with existing processes, as well as potential risks and challenges. The research utilized qualitative analysis using data taken from secondary sources along with interviews with 3 stakeholders chosen with purposeful sampling and observations conducted on internal processes. The results demonstrate that JDE's existing financial reporting approach mainly relies on manual tasks, leading to inefficiencies and a lack of analytical power. Insights from JDE stakeholders also highlight the necessity of increased productivity, automation, better visualizations, and user-friendly navigation. To solve this, Power BI can meet JDE’s needs by simplifying data integration, enhancing data visualization and analysis, minimizing human labor and mistakes, and optimizing the delivery of financial reports. However, the paper also emphasizes possible risks that must be anticipated by risk management controls. Overall, JDE may implement better financial reporting practices while using fewer resources by efficiently utilizing Power BI's capabilities according to needs and addressing potential risks.Keywords: Power BI, Automation, Efficiency, Financial analysis, Finance reporting.